Quantitative study of valence and configuration interaction parameters of the Kondo semiconductors CeM 2Al 10 (M=Ru, Os and Fe) by means of bulk-sensitive hard X-ray photoelectron spectroscopy - Strigari, Fabio; Haverkort, Maurits W. (Journal of electron spectroscopy and related phenomena, 2015)
The occupancy of the 4fn contributions in the Kondo semiconductors CeM2Al10 (M=Ru, Os and Fe) has been quantitatively determined by means of bulk-sensitive hard X-ray photoelectron spectroscopy (HAXPES) on the Ce 3d core levels. Combining a configuration interaction scheme with full multiplet calculations allowed to accurately describe the HAXPES data despite the presence of strong plasmon excitations in the spectra. The configuration interaction parameters obtained from this analysis - in particular the hybridization strength Veff and the effective f binding energy Δf - indicate a slightly stronger exchange interaction in CeOs2Al10 compared to CeRu2Al10, and a significant increase in CeFe2Al10. This shows the existence of a substantial amount of Kondo screening in these magnetically ordered systems and places the entire CeM2Al10 family in the region of strong exchange interactions.